Bis(amidophenolato)phosphonium: Si−H Hydride Abstraction and Phosphorus‐Ligand Cooperative Activation of C−C Multiple Bonds. Issue 8 (16th December 2022) - Roth, Daniel; Thorwart, Thaddäus; Douglas, Clara; Greb, Lutz
Abstract: The first bis(amidophenolato)phosphonium salts are prepared and fully characterized. The perfluorinated derivative represents the strongest monocationic phosphorus Lewis acid on the fluoride and hydride ion affinity scale isolable to date. This affinity enables new reactions, such as hydride abstraction from Et3 SiH, the first phosphaalkoxylation of an alkyne or a phosphorus catalyzed intramolecular hydroarylation. All properties and reactions are scrutinized by theory and experiment. Substantial σ‐ and π‐acidity provides the required affinity for substrate activation, while phosphorus‐ligand cooperativity substantially enriches the reactivity portfolio of phosphonium ions. Abstract : The first donor‐free bis(amidophenolato)phosphonium ions were prepared, and their reactivity was investigated. The compounds possess extreme Lewis acidity up to the strongest monocationic phosphonium‐based fluoride ion acceptor isolable to date. Numerous novel phosphorus‐ligand cooperative reaction modes were observed toward silanes and unsaturated carbon‐carbon bonds.